Mechanical properties of tapioca starch-based film incorporated with bulk chitosan and chitosan nanoparticle: a comparative study - Ahmad Shapi'i, Ruzanna; Othman, Siti Hajar; Naim, Mohd Nazli; Kadir Basha, Roseliza (Universiti Putra Malaysia Press, 2019)
Tapioca starch-based film exhibits poor mechanical properties, thus limiting the application of the film as food packaging material. The present study aims to improve the mechanical properties of tapioca starch-based film by varying the concentration of glycerol (0, 5, 10, 15, 20, 25% w/w). Then, the starch-based films were incorporated with bulk chitosan (CH) and chitosan nanoparticle (CNP) to produce the starch/CH film and starch/CNP film, respectively. The mechanical properties of all the films which are tensile strength (TS), elongation at break (EAB), and Young's modulus (YM) were characterised using texture analyser. The morphological properties of both CH and CNP were observed under scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The results revealed that 25% w/w of glycerol was sufficient to overcome the brittleness of film and improve the flexibility of the film. The addition of CH and CNP led to the increment in TS and EAB values of the films, thus confirming the role of the reinforcing agent of both CH and CNP in the films. A comparison study between CH and CNP demonstrated that CNP was more effective to improve the mechanical properties of the starch films compared to CH.